THE INFLUENCE OF LEVERAGE, FINANCIAL DISTRESS AND TRANSFER PRICING ON TAX AVOIDANCE - Angela, Vena; Frederica, Diana (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Taxes are an expense for company which is in financial statement will reduce a net profit, so that the company will pay a tax expense as low as they can to get a maximum profit. Therefore, this study aims that I take to analyze the influence of Leverage, Financial Distress and Transfer Pricing on Tax Avoidance in mining companies listed on the Indonesia Stock Exchange with research period during 2017-2021. The Sampling of this study using purposive sampling method and obtained 20 companies with 88 sample. The technique that used in this study is date panel regression analysis with Eviews 12 Software. The result of this study indicate there is no influence between Leverage and Transfer Pricing on Tax Avoidance. Meanwhile, on the other hand, there is an influence between Financial Distress on Tax Avoidance.